Reversible addition-fragmentation chain transfer synthesis of amidine-based, CO2-responsive homo and AB diblock (Co)polymers comprised of histamine and their gas-triggered self-assembly in water - Quek, J.; Roth, P.; Evans, R.; Davis, T.; Lowe, Andrew (2013)
Well-defined homopolymers of pentafluorophenyl acrylate (PFPA) and AB diblock copolymers of N,N-dimethylacrylamide (DMA) and poly(ethylene glycol) methyl ether acrylate (PEGA) with PFPA were prepared by reversible addition–fragmentation chain transfer (RAFT) radical polymerization. Three PFPA homopolymers of different molecular weights were reacted with the commercially available amidine and guanidine species histamine (HIS) dihydrochloride and L-arginine methyl ester (ARG) dihydrochloride in the presence of S-methyl methanethiosulfonate to yield, quantitatively, the corresponding amidine and guanidine-based acrylamido homopolymers. Both the HIS and ARG homopolymers are known to reversibly bind CO2 with, in the case of the former, CO2 fixation being accompanied with a switch from a hydrophobic to hydrophilic state. The RAFT synthesis of PFPA-DMA and PEGA-PFPA diblock copolymers yielded well-defined materials with a range of molar compositions. These precursor materials were converted to the corresponding HIS and ARG block copolymers whose structure was confirmed using 1H NMR spectroscopy. Employing a combination of dynamic light scattering and transmission electron microscopy, we demonstrate that the DMA-HIS and PEGA-HIS diblock copolymers are able to undergo reversible and cyclable self-directed assembly in aqueous media using CO2 and N2 as the triggers between fully hydrophilic and amphiphilic (assembled) states. For example, in the case of the 54:46 DMA-HIS diblock, aggregates with hydrodynamic diameters of about 40.0 nm are readily formed from the molecularly dissolved state.